PENGARUH METODE PENGERINGAN TERHADAP KUALITAS EKSTRAK DAN KADAR FLAVONOID TOTAL EKSTRAK ETANOLIK DAUN SAMBUNG NYAWA (Gynura procumbens (Lour.) Merr.) - Retno Priamsari, Margareta; Mita Susanti, Maria; Harya Atmaja, Andreas (Jurnal Farmasi (Journal of Pharmacy), 2016)
Flavonoids is one active compounds in the Gynura procumbens (Lour.) Merr. leaves for antioxidant, inhibiting of cancer cells, and maintaining liver function. Flavonoid is thermolabile compound and need proper post harvest handling. The purpose of this study is to the determine effect of drying method on the quality of extract and total flavonoids content in ethanolic extract of Gynura procumbens (Lour.) Merr. leaves. This type of research is experimental. Drying methods used in this research are by wind drying under shade place from direct sunlight and oven drying in 40o C temperature. Analysis of total flavonoids content using colorimetric method with AlCl3 complexing compounds and quercetin standard. Standard calibration curve was made 5 series concentrations of 40, 60, 80, 100, and 120 ppm. The absorbance was read at 434 nm wavelength of Uv Vis spectrophotometer. Data obtained in the form of lower levels of flavonoids are analyzed statistically with a pair of independent sample t -test. The results showed if drying methods make a significant different of quality extract and total flavonoids content ethanolic extract of Gynura procumbens (Lour.) Merr leaves. Total flavonoids content with wind drying method is 2.15 ± 0.03% w/w and total flavonoid content with 40oC oven drying method is 1.87 ± 0.01% w/w. The total flavonoid content is counted as quercetin.